The potential to improve ascertainment and intervention to reduce smoking in Primary Care: a cross sectional survey - Fergus Alexia; Antoniak Marilyn; Coleman Tim; Murray Rachael L; Britton John; Lewis Sarah A (BMC, 2008)
Abstract Background Well established clinical guidelines recommend that systematic ascertainment of smoking status and intervention to promote cessation in all smokers should be a fundamental component of all health care provision. This study aims to establish the completeness and accuracy of smoking status recording in patients' primary care medical records and the level of interest in receiving smoking cessation support amongst primary care patients in an inner city UK population. Methods Postal questionnaires were sent to all patients aged over 18 from 24 general practices in Nottingham UK who were registered as smokers or had no smoking status recorded in their medical notes. Results The proportion of patients with a smoking status recorded varied between practices from 42.4% to 100% (median 90%). Of the recorded smokers who responded to our questionnaire (35.5% of the total), a median of 20.3% reported that they had not smoked cigarettes or tobacco in the last 12 months. Of respondents with no recorded smoking status, 29.8% reported themselves to be current smokers. Of the 6856 responding individuals thus identified as current smokers, 41.4% indicated that they would like to speak to a specialist smoking adviser to help them stop smoking. This proportion increased with socioeconomic disadvantage (measured by the Townsend Index) from 39.1% in the least deprived to 44.6% in the most deprived quintile. Conclusion Whilst in many practices the ascertainment of smoking status is incomplete and/or inaccurate, failure to intervene appropriately on known status still remains the biggest challenge. Trial registration Current Controlled Trials ISRCTN71514078.